The wide window ebook - Snicket, Lemony (A Series of Unfortunate Events, 2009)
NOW A NETFLIX ORIGINAL SERIES Dear Reader, If you have not read anything about the Baudelaire orphans, then before you read even one more sentence, you should know this: Violet, Klaus, and Sunny are kindhearted and quick-witted, but their lives, I am sorry to say, are filled with bad luck and misery. All of the stories about these three children are unhappy and wretched, and this one may be the worst of them all.If you haven't got the stomach for a story that includes a hurricane, a signalling device, hungry leeches, cold cucumber soup, a horrible villain, and a doll named Pretty Penny, then this book will probably fill you with despair.I will continue to record these tragic tales, for that is what I do. You, however, should decide for yourself whether you can possibly endure this miserable story. With all due respect, Lemony Snicket